Crianças, infâncias e avaliação formativa: o que dizem as pesquisas desenvolvidas no Grupo de Estudos e Pesquisas em Avaliação Educacional – Gepae/UFU - Rodrigues, Mara Cristina Oliveira (2022)
This dissertation is linked to the research line Knowledge and Educational Practices, of the Graduate Program in Education (PPGED), of the Federal University of Uberlândia (UFU) and addresses the work carried out by the Group of Studies and Research in Educational Assessment (Gepae/UFU), focusing especially on understanding conceptions of children, childhood and formative evaluation in Master's and Doctoral research developed in this Group. Based on this purpose, it was possible to raise the following question: what researches, especially Master's and Doctoral works, produced within the scope of Gepae/UFU, have discussed about children, childhood and formative evaluation? Based on this question, the general objective was to study the research, especially in the Master's and Doctoral scopes, produced by Gepae/UFU and to analyze how this Group positions itself on children, childhood and formative evaluation. Considering this main purpose, it was also intended to describe the history of Gepae/UFU; carry out a general survey on the production of Gepae/UFU; to select the Master's and Doctoral works carried out by the Group's components to analyze their conceptions and positions on children, childhood and formative evaluation; in addition to analyzing the contributions of these researches to the work with children, with childhoods and with formative evaluation. The present investigation is based on a perspective that emphasizes the production of knowledge as an objective and subjective, descriptive and interpretive historical process and materialized through the accomplishment of a bibliographic work. Our analysis allowed us to conclude that the concept of evaluation is predominant in the investigations developed at Gepae/UFU, demonstrating the commitment of this Group to the theme. In addition, it was also possible to verify that the study of evaluation is focused on the design of formative evaluation and that the research focused on three themes: conceptions of evaluation and formative evaluative praxis, external evaluation and formal and informal evaluation processes. In this way, these researches sought to analyze, identify and understand evaluation conceptions and practices in force in public schools and at the university, as well as external evaluation has impacted the organization of pedagogical work and the evaluation developed in public schools. In addition, the focus of these researches is directed towards teachers and/or professors and students. It is worth noting the care with language and gender representation in the productions developed at Gepae/UFU. The analyzed data also allow us to affirm that this Group considers that formative evaluation contributes to the educational process developed in schools, since this assessment is based on principles that allow students and teachers to make progress and also informs about the limits of the work carried out and about possibilities to redirect the pedagogical work. The term “children” is mentioned explicitly in only one research, however, the presence of this term was identified, in a secondary way, in the body of other studies. These researches mention children as subjects of law, subjects who have knowledge and experiences; however, they do not appear as subjects in the research. The term “childhood” or “childhoods” also appears in a secondary way in the surveys. In view of the above, it can be highlighted that Gepae/UFU presents important concepts and notes regarding formative assessment, the quality of socially referenced Education and the defense of public schools.